Techniques for selecting learning media in Madrasah Ibtidaiyah educational institutions - Hilman, Cecep; Rohmah, Siti; Syarifah, Maulida (C-DISC, 2025)
This study aims to examine the techniques for selecting learning media in Madrasah Ibtidaiyah educational institutions through a literature review approach. This method involves the collection and analysis of data from various literature sources such as books, articles, and journals related to learning media. The selection of learning media in Madrasah Ibtidaiyah is influenced by several important factors, including student characteristics, learning objectives, the availability of technology, and the material being taught. This study found that challenges in selecting learning media often relate to resource limitations and access to technology. Therefore, enhancing teachers' abilities to use various media effectively is highly recommended to improve the quality of learning in Madrasah Ibtidaiyah.